LIFESTYLES AND HEALTH BEHAVIOURS OF YOUNG ADULTS WITH TYPE 1 DIABETES IN PORTUGAL - Nabais, Joao (2014)
Background: Adherence to diabetes management and the quality of life of young adults with type 1 diabetes can be affected by the several changes occurring during emerging adulthood: social, occupational, familiar and emotional. Aims: Evaluation of lifestyles, health behaviours, treatment adherence and social support of young adults with type 1 diabetes. Participants: 278 young adults with type 1 diabetes, aged between 18 - 35, attending the Portuguese Diabetes Association. Methods: A questionnaire with 63 questions was completed by young adults. This is a quantitative research with descriptive and correlational analysis. Results: The participants reported satisfaction with life as 6.6 ±1.7 (scale 0-10). They reported healthy eating habits and one third of them practice recommended physical activity. Adherence to insulin therapy and glucose monitoring was satisfactory; however the mean value for HbA1c was 8.7% ±1.6 with highest HbA1c levels being related to less glucose monitoring and insulin administration. The best representations about diabetes were positively correlated with adherence to nutrition and insulin therapy. These young adults reported good social support and refer the benefits of group activities with peers. Conclusions: Young adults showed satisfactory social support, health behaviours and satisfaction with life and a reasonable adherence to diabetes treatment, although with a less satisfactory metabolic control of diabetes. Further research with focus groups will help to better understand these discrepancies.